Ethanol as additive enhances expression of Ranibizumab in Escherichia coli: Impact on cellular physiology and transcriptome. (January 2022) - Priyanka, Priyanka; Patil, Rucha S.; Meshram, Pradnya; Gupta, Jaya A.; Banerjee, Manidipa; Rathore, Anurag S.
Graphical abstract: Highlights: Effect of various chemical additives on recombinant Ranibizumab expression were investigated. The effect of ethanol (as additive) on cell size, cellular physiology and cellular viability were examined. A 2-fold improvement in recombinant Ranibizumab expression has been demonstrated. Correct folding and activity of recombinant Ranibizumab confirmed using LC–MS and SPR. Abstract: Ranibizumab is an antibody fragment used for treatment of blurred vision due to age-related macular degeneration. Most manufacturers currently express it in Escherichia coli BL21 (DE3), where low-level expression of this complex protein has been acknowledged to result in higher production cost. This paper aims to present a strategy involving the use of additives with previously developed clone of Ranibizumab to enhance its expression in E. coli . The effect of ethanol (as additive) on cell size (control 1.82 μm and optimized 2 μm), cellular physiology (no cell swelling, or shrinkage observed) and cellular viability (better in optimized sample) were examined. A 2-fold improvement in Ranibizumab expression has been demonstrated (from 0.23 mg/mL to 0.48 mg/mL in single copy clone and 0.4 mg/mL to 0.72 mg/mL in double copy clone) using the optimized conditions vis-a-vis the control, thereby demonstrating the efficacy of the proposed approach. LC–MS confirmed correct disulfide bond formation and surface plasmon resonance confirmed the formation of active recombinant protein via binding to its target VEGF (KD = 12.7 nM). Transcriptomic analysis and RT-qPCR validation indicated that changes in membrane properties and DNA synthesis results in growth, gene amplification and enhances synthesis of inducible proteins in case of the optimized medium.